New advances in the diagnosis and treatment of pediatric tuberculosis. (January 2013) - Cruz, Andrea T; Mandalakas, Anna M
Childhood tuberculosis (TB) remains a disease that causes substantial global morbidity and mortality. In the last decade, advances in immunologic and PCR-based testing have promised to improve our ability to prevent disease by identifying and treating latent TB infection and enabling earlier recognition of disease, respectively. Nevertheless, TB diagnostic and therapeutic research in children has been limited and poorly harmonized due to the lack of a standardized approach. Only recently has the scientific community arrived at consensus regarding a standard case definition of intrathoracic disease and developed guidelines to support a standardized approach for the evaluation of new TB diagnoses in children. These two events have set the stage for a new era in pediatric TB research. In this article we will summarize the performance of new diagnostics (IFN-γ release assays and GeneXpert ® ) in children, as well as review available treatment regimens for children with latent TB infection and disease.